Symptomatic sacral perineurial (Tarlov) cysts - Sajko, Tomislav (Array, 2009)
Abstract: Sacral perineurial (Tarlov) cysts are rare lesions. Over a seven year period 4000 patients underwent surgery for lumbar disk herniation. In three patients neurological symptoms were caused by large sacral perineurial cysts. Methods of choice for diagnosis of Tarlov cysts are lumbosacral magnetic resonance imaging and computerized tomography myelography. The majority of Tarlov cysts are asymptomatic. In case of large (ł1.5 cm) and symptomatic perineurial cyst, as in three patients reported in this article, microsurgical treatment was successful. Although rare, perineurial (Tarlov) cysts must be taken into consideration when approaching to patient with low back and radicular pain. Authors review the medical literature, pathological and pathophysiological features and treatment options of sacral perineurial cysts